SYMBOLIC INTERACTION AS A CONNECTION BETWEEN SELF-ONLINE PRESENTATION AND TRENDS TO BE CYBERBULLYING PEOPLE YOUTH IN THE CITY OF MEDAN - Donna Isra Silaban (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
Objective: The study was conducted to determine the relationship between variable symbolic interaction, online self presentation and the tendency to be cyberbullying. It is assumed that there is a positive and significant relationship between online self presentation (X) and the tendency to be cyberbullying (Y) mediated by symbolic interaction (M). Method: The study involved 435 respondents. The instrument is an adaptation of Manford Kuhn's Twenty Statement Self Attitude Test, Mayawati's (2016)online self-presentation scale and the tendency to become cyberbullying Lesbassa's (2014) scale. Mediator analysis was processed using SmartPLS. Results: The direct effect coefficient between online self presentation and symbolic interaction is 4,304; the direct effect coefficient between online self presentation and the tendency to be cyberbullying is 2,665; the direct effect coefficient between symbolic interactions and the tendency to be cyberbullying is 2,674. While the indirect effect coefficient between online self presentation and the tendency to be an actor through symbolic interaction is 2,271. Based on the results of the test found the overall value of T Statistics> T-table (1.96). So that it can be seen that online self presentation and the tendency to be cyberbullying shows a positive and significant relationship in adolescents in Medan City through symbolic interactions.